To determine the length of over penetration during drilling procedure with K wire and Drill Bit among orthopaedic's master student Universiti Sains Malaysia - Wan Mohd Shaifulnizam, Che Wan Nik (2009)
Drilling procedure is the most fundamental surgical skill required by orthopaedic surgeon as many fractures nowadays are treated operatively. Neurovascular injuries are known to be as one of the complications of over penetration drilling. The purpose of this study is to determine the length of over penetration in drilling technique among orthopaedic's master students Universiti Sains Malaysia. Fourteen juniors (Post Graduate Year 1 and 2) and fourteen seniors (Post Graduate Year 3 and 4) were recruited in this study. They performed drilling procedure on the bovine bone block using battery powered drill with 3.2mm drill bit and 2.0mm K wire. Drilling was stopped immediately once they felt the penetration of far cortex. The distance from the instrument's tip to the far cortex was measured. The procedure was repeated three times and means values were calculated. The lengths of over penetration results from the two instruments were compared using parametric paired t-test. The lengths of over penetration results in "Experience Level" group and "Exposure to AO course" group for each drilling instrument were compared by using non parametric Mann-Whitney U test. The mean length of over penetration for drill bit and K-wire were 21.50 mm (10.33-35.66 mm) and 10.18 mm (3.00-18.66 mm) respectively. Using drill bit, the median length of over penetration for junior group and senior group were 25.55 mm and 16.66 nun respectively. With K wire, the median length of over penetration for junior group and senior group were 16.50 mm and 5.50 mm respectively. For group exposed to AO course, the median length of over penetration was 13.33 nun with drill bit and 5.00 mm with K wire. Those without exposure to AO course, the median length of over penetration was 21.66 mm with drill bit and 10,66 mm with K wire. The differences were statistically significant with regard to the instrument's type and "experience level" (all p<O.OOl). The differences were also statistically significant with regard to "exposure to AO course" group: p=0.02 with drill bit and p=0.05 for K wire There was a significant correlation between training years in Post Graduate USM with personal experience in Orthopaedic. Our study provides the overall result regarding the depth of over penetration in drilling procedure among orthopaedic's master student Universiti Sains Malaysia. It may benefit as the reference for related study in the future.